1996
DOI: 10.1002/(sici)1096-9861(19961014)374:2<204::aid-cne4>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic inputs to the nucleus rotundus (pulvinar inferior) of the pigeon (Columba livia)

Abstract: The avian nucleus rotundus, a nucleus that appears to be homologous to the inferior/ caudal pulvinar of mammals, is the major target of an ascending retino-tecto-thalamic pathway. Further clarification of the inputs to the rotundus and their functional properties will contribute to our understanding of the fundamental role of the ascending tectal inputs to the telencephalon in all vertebrates, including mammals. We found that the rotundus contains a massive plexus of glutamic acid decarboxylase (GAD)-immunorea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 26 publications
6
103
0
1
Order By: Relevance
“…Given that the nRT contains several distinct areas on the basis of neurochemistry, cytoarchitecture, tectal innervation, and physiology Benowitz and Karten, 1976;Revzin, 1979;Watanabe et al, 1985;Martinez-de-la-Torre et al, 1990;Wang et al, 1993;Mpodozis et al, 1996;Marin et al, 2003) and that the topographic nRT-Ec projection may be quite precise (Husband and Shimizu, 1999;Laverghetta and Shimizu, 2003), it is proba- Figure 4. Correlation between performance and the extent of the lesion in Ec.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Given that the nRT contains several distinct areas on the basis of neurochemistry, cytoarchitecture, tectal innervation, and physiology Benowitz and Karten, 1976;Revzin, 1979;Watanabe et al, 1985;Martinez-de-la-Torre et al, 1990;Wang et al, 1993;Mpodozis et al, 1996;Marin et al, 2003) and that the topographic nRT-Ec projection may be quite precise (Husband and Shimizu, 1999;Laverghetta and Shimizu, 2003), it is proba- Figure 4. Correlation between performance and the extent of the lesion in Ec.…”
Section: Discussionmentioning
confidence: 83%
“…On the basis of neurochemistry, cytoarchitecture, tectal innervation, and physiology, nRT has been divided into several subnuclei (Benowitz and Karten, 1976;Martinez-dela-Torre et al, 1990;Mpodozis et al, 1996;Marin et al, 2003). Early electrophysiological studies showed that the majority of cells in nRT were motion sensitive (Revzin, 1979).…”
Section: Introductionmentioning
confidence: 73%
“…This asymmetry suggests that the E in barn owls is mainly involved in visual and not auditory processing. Because we did not systematically survey the E, we cannot rule out the possibility that it is functionally divided into subregions with different modality preferences, consistent with the idea that the tectofugal pathway is functionally segregated (Benowitz and Karten, 1976;Mpodozis et al, 1996;Karten et al, 1997). Despite the relatively weak influence of auditory signals alone, congruent auditory stimuli presented simultaneously with the visual stimuli substantially enhanced the visual SSA effects.…”
Section: Discussionmentioning
confidence: 99%
“…This parceling into parallel pathways originates in the OT in which different subclasses of TGCs project to separate regions in nRt (Benowitz and Karten, 1976;Mpodozis et al, 1996;Karten et al, 1997;Marín et al, 2003). It is possible that the bimodal information we report here is originating in a subclass of multisensory TGCs and is transferred alongside other visual pathways.…”
Section: The Avian Tectofugal Pathwaymentioning
confidence: 99%